ANALISIS BEBAN PENDINGINAN PADA RUANG PENYIMPANAN PRODUK PERTANIAN UNTUK SULAWESI UTARA DENGAN MENGGUNAKAN SISTEM REFRIGERASI BERTINGKAT - Yosua A P Tondok; Hengky Luntungan; Benny Lokombanua Maluegha (JURNAL POROS TEKNIK MESIN UNSRAT, 2017)
This research aims to calculate the cooling load in cold storage of some agricultural products: potatoes, tomatoes, and peppers; to calculate the compressor’s power that is used on the cold storage with three types of multistage compression system: two compressors – three evaporators system (type 1), one compressor – three evaporators system (type 2), and two compressors – one evaporator system (type 3) for each agricultural products; and to analyze the calculated compressor’s power to determine the most efficient refrigeration system.Based on the calculation’s results, it is found that the cooling load of potatoes is 295.438,28 Btu/hour, tomatoes 247.261,38 Btu/hour, peppers 300.281,36 Btu/hour, and the total cooling load of the three agricultural products is 841.981,02 Btu/hour. By using multistage compression system, it is obtained that the compressor’s power of type 1 is 106,15 hp, type 2 108,55 hp, and the type 3 212,03 hp that consists of type 3a is 75,55 hp, type 3b 59,44 hp, and type 3c 77,04 hp. Keywords: cooling load, multistage compression system, compressor’s power